Peran Orang Tua dalam Meningkatkan Kemampuan Membaca Permulaan di Sekolah Dasar - Yoga Adi Pratama; Wagiran Wagiran; Haryadi Haryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
As a language skill, reading is a complex thing to master. A person's reading ability is passed through the stages of initial reading and advanced reading. Beginning reading is given to students I and II while continuing reading is given to students in grades III, IV, V, and VI. Beginning reading ability is the competency possessed by students in reciting symbols in a clear and precise voice. Therefore, beginning reading becomes something that is important for students to master before acquiring/learning advanced reading. Beginning reading mastery is strongly influenced by how the teacher is able to develop various approaches, methods and strategies used in teaching beginning reading. Keywords; Role, Teacher, Parents, Beginning Reading Ability, Elementary School